Application of Learning Media in Improving Higher Order Thinking Skills in Electronics Teaching Materials - Marsangkap Silitonga; Muhammad Dani Solihin; Muhammad Isnaini; Harvei Desmon Hutahaean (Postgraduate, University of Mataram, 2024)
This research aims to create a learning multimedia application that can be used by students in learning. The method used is development research from Jan Van De Akker with formative evaluation from Martin Tessmer. The research stage consists of four stages, namely the preliminary research stage, prototype, summative evaluation, and systematic reflection and documentation. Based on user assessment, the learning multimedia is practical to use with a practicality level of 83% and is included in the good category. The effectiveness of multimedia at the summative evaluation stage is based on the post-test results. The results of the student posttest stated that 9 out of 12 students scored â‰¥75, meaning that 75% of the participants passed and this multimedia is effective. The results showed that the learning multimedia application can improve the higher-order thinking skills of students.